1986
DOI: 10.1002/ardp.19863190316
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Drugs, XI: Diacyl Derivatives of Butyroguanamine

Abstract: ++)Am der Dissertation M. Loch, Mainz 1985. 0365-6233/86/030W3275 $ 02.50/0 8 VCH Verlagsgesellschaft mbH, D-6940 Weinheim, 1986 276 Kreutzberger und Loch Arch. Pharm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…s-Triazine derivatives also possess biological activities, such as anti-tubercular, 5 antitumor, 6 anti-cancer, 7 sedative, 8 anti-inflammatory 9 and anthelmintic 10 activities. In comparison with a previous publication on 1,3,5-triazinyl dithiocarbamates, 11 in which only one molecule of cyanuric chloride was involved in the reported molecules, a recent literature survey revealed that not a single method for the synthesis of bis(4,6-dichloro-1,3,5-triazin-2-yl) 1,2-hydrazine-1,2--dicarbodithioate 4a, 1,4-phenylenebis(carbamodithioate) 4b, (1,1'-biphenyl)-4,4'--diylbis(carbamodithioate) 4c, (sulfonyldi-4,1-phenylene)bis(carbamodithioate) 4d and 1,2-ethanediylbis(carbamodithioate) 4e, nor of bis{4,6-bis[(p-methoxyphenyl)amino]-1,3,5-triazin-2-yl} esters of the respective acids (4f-j) has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…s-Triazine derivatives also possess biological activities, such as anti-tubercular, 5 antitumor, 6 anti-cancer, 7 sedative, 8 anti-inflammatory 9 and anthelmintic 10 activities. In comparison with a previous publication on 1,3,5-triazinyl dithiocarbamates, 11 in which only one molecule of cyanuric chloride was involved in the reported molecules, a recent literature survey revealed that not a single method for the synthesis of bis(4,6-dichloro-1,3,5-triazin-2-yl) 1,2-hydrazine-1,2--dicarbodithioate 4a, 1,4-phenylenebis(carbamodithioate) 4b, (1,1'-biphenyl)-4,4'--diylbis(carbamodithioate) 4c, (sulfonyldi-4,1-phenylene)bis(carbamodithioate) 4d and 1,2-ethanediylbis(carbamodithioate) 4e, nor of bis{4,6-bis[(p-methoxyphenyl)amino]-1,3,5-triazin-2-yl} esters of the respective acids (4f-j) has been reported to date.…”
Section: Introductionmentioning
confidence: 99%